Renda mínima de inserção e transferência condicionada de renda : as (a) simetrias entre União Europeia e MERCOSUL - Guilherme, Rosilaine Coradini (2016)
This thesis involves an analysis about the main (a) symmetries and consequent contradictions implicits in the Minimum Income Insertion Programs, practiced by the European Union countries – EU, against the Conditional Cash Transfer Programs, in execution by the countries of the Southern Common Market – MERCOSUR, inside or between economic blocs, agoing produce oriented knowledge to construct social public redistributive policies guided by the logic of law, whose character be universalist. The problematization process of the study object is guided, epistemologically, in the dialectical-critical method, in reason of a theoretical option and the specificity of the study that presuppose an intrinsic contradiction between State, market and society. In accordance predicts a comparative approach supported by the historical-structural perspective, in addition rely on mixed focus, correlating qualitative and quantitative data, having as a time interval of observation the period 1990-2015. This is a quantitative-qualitative research of exploratory kind, in which the collect of the data is based on documentary and bibliographic source of national and international origin. Regarding the geographical scale of observation, was delimited the States part and associate to MERCOSUR, and EU countries that integrates the named Eurozone, giving emphasis to programs practiced by France and Portugal, as well as the experiences in execution in Chile and Brazil. In the research process it was considered the different historical realities, as a result, the study object revealed heterogeneous, both inside and between economic blocs. It was understood that the underlying contradiction to the related programs resides in the fact that they configure a response secularly used to maintain the concentration of wealth, in the sense that aims to provide cohesion/social integration under the fundamentals of markets economy. Specifically, these related programs, although present a more sophisticated version, they do not constitute innovative measures to combat poverty, on the contrary, because replicate secular methods of regulation of the contradictions arising from the private concentration of wealth, concealing the origins of this acute expression of the social questions. Instead of fighting with structural changes the social inequalities that shape as the various economic cycles and territorial features, (re) edit up with emergency measures enshrining the recoil of the universality principle in favor of focusing. It was put in evidence an issue considered fundamental to be considered, because despite programs, in levels inside and between blocs, reveal disparities regarding the methodological aspects and the contents of the components that structure are symmetrical in terms of structural conception. Which corresponds to the central limit of this public policy that does not constitute an acquired right, in view of the social and financial installment having transitory character, besides are customized to the 'problem' of each individual/families, leading the fragmentation of historical process and, consciously, the social policies. Finally, it was intend to put on schedule the fight against social inequalities under the structural point of view, which matches with the process of changes in the orientation of economic policies that sustain the neoliberal theoretical, inverting the current prevalence of the economic over the social.